2022
DOI: 10.3390/healthcare10101889
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Patient Safety Culture from Nurses’ Perspectives for Sustainable Nursing Practice

Abstract: Individual and group beliefs, attitudes, perceptions, competences, and behavioral patterns all contribute to the safety culture of a healthcare company. The study’s goal is to assess nurses’ perceptions of elements that influence patient safety culture in order to promote long-term nursing practice. A descriptive cross-sectional study design was done among a sample of 146 nurses who were recruited from one hospital in Egypt. They completed a self-administered, printed questionnaire. The questionnaire assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
6
0
1
Order By: Relevance
“…at hospitals (Abdelaliem & Alsenany, 2022). This finding is consistent with and supported by Alharbi et al (2018) and Abdelaliem and Alsenany (2022), who found that the frequency of events reported had a low mean score and was seen as a possible area for improvement.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…at hospitals (Abdelaliem & Alsenany, 2022). This finding is consistent with and supported by Alharbi et al (2018) and Abdelaliem and Alsenany (2022), who found that the frequency of events reported had a low mean score and was seen as a possible area for improvement.…”
Section: Discussionsupporting
confidence: 89%
“…This could be due to poor communication, intense time constraints on staff and economic factors such as the ineffective use of resources (budget, supplies and materials). These result in precarious situations for nurses and sub‐optimal care, and nurses may be reluctant to discuss and report events that might happen at hospitals (Abdelaliem & Alsenany, 2022). This finding is consistent with and supported by Alharbi et al (2018) and Abdelaliem and Alsenany (2022), who found that the frequency of events reported had a low mean score and was seen as a possible area for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result revealed that several errors occurred to patients & health care workers per year fewer than two-thirds, this result was congruent with Abdelaliem & Alsenany (41) found that less than a quarter of participants mentioned that event reports yearly were less than 3 and fewer than half perceive patient safety as excellent and about few percent show, it is either acceptable and or poor. Likewise, our result agreed with Ali, et al (42) found that less than one-third of the participants did not report any event, while 69.7% reported from one to more than 11 event reports.…”
Section: Discussionsupporting
confidence: 88%
“…Guaranteeing people’s healthy lives and patient and personnel safety and improving healthcare quality to create an effective healthcare system is crucial for maintaining high living standards. [ 1 , 2 ] Given the technological revolution in the healthcare industry and the need to meet health quality standards for maintaining high-quality services. [ 3 ] Healthcare services management has become challenging in this setting.…”
Section: Introductionmentioning
confidence: 99%